2018
DOI: 10.1080/10942912.2018.1517782
|View full text |Cite
|
Sign up to set email alerts
|

Essential oil composition, phenolic compound, and antioxidant potential of Inulaviscosa as affected by extraction process

Abstract: The purpose of this study was to compare the essential oil composition of Inula viscosa leaves by hydrodistillation (HDE), ultrasonic (UDE) and solvent (SE) extractions followed by hydrodistillation. The total polyphenol and flavonoid contents and their antioxidant effects were studied by different solvent of extraction: ethanol (ET), ethyl acetate (EA), methanol (ME) and aqueous (AE). The principal compounds for HDE were: 2-hexenal (3.70%), caryophyllene oxide (3.11%), γ-selinene (3.09%), 3-hexen-1-ol (2.00%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 38 publications
(49 reference statements)
0
9
0
Order By: Relevance
“…This disadvantage restricts its application for thermolabile compound extraction. Sriti Eljazi et al () described that the extraction yields of flavonoids including luteolin with HDE are higher as compared with the MAE and ME.…”
Section: Extraction Techniquesmentioning
confidence: 99%
“…This disadvantage restricts its application for thermolabile compound extraction. Sriti Eljazi et al () described that the extraction yields of flavonoids including luteolin with HDE are higher as compared with the MAE and ME.…”
Section: Extraction Techniquesmentioning
confidence: 99%
“…The lipophilic (essential oil) and hydrofracture (hydrosol) collected from the inner tube of the Clevenger apparatus differ in chemical composition and biological activity due to the difference in solubility of the volatile compounds. In addition to water distillation, some authors have performed steam distillation, solvent extraction, and extraction by ultrasonic distillation from plant material of the genus Inula [8][9][10]. They obtained significant differences in the yield and composition of the essential oil [8].…”
Section: Gas Chromatography and Mass Spectrometry (Gc-ms) Analysis Of The Free Volatile Compounds From Essential Oil And Hydrosolmentioning
confidence: 99%
“…As an aromatic species with intense odor, this plant has been the subject of phytochemical profiling of volatile components performed by steam distillation, solvent extraction, and extraction by ultrasonic distillation [8][9][10]. The composition of the essential oil of D. viscosa is described in a large number of scientific papers and the main components of the essential oil obtained from different countries and regions are listed in the work of Zouaghi et al [8].…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the reflux technique using methanol as a solvent is better than the other extraction techniques [234]. Hydrodistillation was also used for flavonoids extraction including luteolin [235]. Besides, microwave-assisted extraction technique was employed in extraction of luteolin, and it was reported that this method is more efficient and produced higher extraction yield compared to maceration and heat reflux extraction methods [233].…”
Section: Luteolinmentioning
confidence: 99%